TOWARDS AN IMPROVEMENT OF PATIENT SAFETY: A FRAMEWORK FOR CLINICAL DECISION SUPPORT SYSTEMS - Macedo, Mário (2017)
Patient safety is a very important issue. The patient’s expectations are a correct diagnosis and an efficient and effective treatment plan, while healthcare providers are balancing costs with the quality of the services. The payers are interested to getting the maximum return for their investments and operational costs. All these issues point to the fact that healthcare providers should follow best practices and resources allocation of resources must be planned according to the predicted needs. Clinical Decision Support Systems (CDSS) can recommend practices according to accepted guidelines that have been previously defined, validated and approved and these systems should be the “compass” for health professionals. The guidelines should be uploaded to the health facility computer systems and written in languages that can be shareable and processed by different software applications. This paper presents a case study that includes a review of the main features of a syntax to describe clinical guidelines and a framework of concepts, methodologies and technologies to improve the clinical decision support systems (CDSS).